Further Evidence on the Determinants of Municipal Audit Fees. - Ward, D. Dewey; Elder, Randal J. (The Accounting Review, 1994)
Abstract Develops a municipal audit fees model which incorporates additional variables that reflect unique aspects of the municipal accounting and auditing environment. Fee model for a sample of Michigan municipalities; Association of audit fees with the number of audit adjustments; Agency and political costs; Political competition; Auditor experience; Opinion qualifications.